The Ocean and Cryosphere in a Changing Climate in Latin America: Knowledge Gaps and the Urgency to Translate Science Into Action - Muelbert, Mônica M. C.; Copertino, Margareth; Cotrim da Cunha, Leticia; Lewis, Mirtha Noemi; Polejack, Andrei; Peña-Puch, Angelina del Carmen; Rivera-Arriaga, Evelia (Frontiers in Climate, 2021)
Climate Change hazards to social-ecological systems are well documented and the time to act is now. The IPCC-SROCC used the best available scientific knowledge to identify paths for effective adaptation and mitigation of climate change impacts on the ocean and cryosphere. Despite all the evidence and invaluable services the ocean and cryosphere provide to society, countries have adopted diverse actions with respect to Climate Change as a result of information not readily available, accessible, and inclusive to policy makers. Skewed geographical and technological gaps of knowledge on key ecosystems and specific areas due to regional imbalance in economic development, technological level, capacity development, societal involvement, and governmental oversight also contribute. Moreover, society’s participation in knowledge production and provision enhances communication pathways, climate literacy and engagement. Citizen science and integration of traditional and local knowledge are key to transforming changes to be reflected in governance. Inclusion and equity require accessible language and capacity development. We discuss whether SROCC’s findings have been addressed in LA and argue the need for: (i) long-term engagement from governments and policymakers along with scientific involvement and participation in integrated climate change mitigation, (ii) integration of scientific, local and indigenous knowledge, and (iii) public engagement to transform consumption patterns, climate education, social innovation and technologies. Currently, the lack of accessible and inclusive information at the local level hampers the overall understanding, integration and engagement of the society to mitigate climate effects, perpetuates regional heterogeneity and threatens the efforts to reverse the course of climate change in LA.